THE INFLUENCE OF SEAFARER RECRUITMENT AND SELECTION SYSTEM QUALITY ON OPERATIONAL PERFORMANCE EFFECTIVENESS: AN EMPIRICAL STUDY AT PT CEMERLANG MAKMUR ABADI - Hisra, Maudhika Putri; Kisman, Zainul; Abdullah, Zed (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2025)
Effective human resource management is a cornerstone for operational sustainability, particularly in the maritime industry, which demands high precision and strict adherence to safety protocols. This study investigates the influence of the recruitment and selection systems on the operational performance effectiveness of seafarers at PT Cemerlang Makmur Abadi. Employing a quantitative approach and analyzing data from 60 seafarer respondents using Partial Least Squares - Structural Equation Modeling (PLS-SEM), the findings reveal that the recruitment system has no significant influence (t=1.050, p>0.05) on operational performance. Conversely, the selection system demonstrates a positive and significant influence (t=2.511, p<0.05). This result strongly suggests that the in-depth screening process during the selection phase plays a far more critical role than the initial candidate attraction process. The practical implication is the necessity of optimizing the selection process to ensure the competence of seafarers, which ultimately enhances productivity, efficiency, and work safety.